Optimisation of the compatible retrofitting measures to enhance the Environmental performance of Heritage Buildings: A DSS-Based Evaluation - Fenk D. Miran; Husein A. Husein (Zanco Journal of Pure and Applied Sciences, 2025)
This study addresses the challenge of balancing heritage conservation with modern environmental performance requirements by developing a Decision Support System (DSS) to aid in selecting the most effective retrofitting strategies for heritage buildings. The lack of a standardized, adaptable framework for optimizing retrofitting solutions highlights the need for a robust assessment tool. Despite the availability of multiple retrofitting strategies, heritage buildings require a systematic approach to selecting interventions that align with conservation principles while optimizing environmental performance. Current methodologies lack a decision-making framework that integrates heritage significance and environmental impact, while also considering economic feasibility. This study fills this gap by developing a DSS tailored for heritage retrofitting. To achieve this, the study employed a mixed-methods approach, integrating both qualitative and quantitative research methods to establish a robust DSS framework. The DSS evaluates various retrofitting options based on three essential criteria: heritage preservation, environmental impact, and economic viability. Additionally, expert insights were incorporated through a structured questionnaire, and the EFFESUS (Energy Efficiency for EU Historic Districts’ Sustainability) project methodology was adapted for the scoring and weighting system to enhance the tool’s reliability. The DSS evaluation identified Liquid Waterproofing Membrane as the most effective solution for moisture management, Aerogel Insulation as the optimal choice for thermal regulation, and Double Glazing with Low-E Coating as the best strategy for energy-efficient window retrofitting. These findings confirm the DSS’s ability to systematically assess retrofitting measures while preserving heritage integrity. The study is limited to selected retrofitting interventions within the context of Erbil’s heritage buildings, and further validation in diverse heritage settings is required to enhance the DSS’s applicability. This research contributes to the expanding field of sustainable architectural conservation, offering practical insights and a strategic framework for optimizing retrofitting interventions in heritage buildings.